Environmental heterogeneity modulates the effect of plant diversity on the spatial variability of grassland biomass - Pedro Daleo; Juan Alberti; Enrique J. Chaneton; Oscar Iribarne; Pedro M. Tognetti; Jonathan D. Bakker; Elizabeth T. Borer; Martín Bruschetti; Andrew S. MacDougall; Jesús Pascual; Mahesh Sankaran; Eric W. Seabloom; et al. (Nature Communications, 2023)
The insurance hypothesis posits that more diverse communities are more stable through time. Here, the authors show that plant biodiversity reduces the spatial variability of productivity in grassland communities, demonstrating that the insurance hypothesis applies also across space.